Treatment of non-traumatic occlusions: Round table conclusions Raúl Ugarte Artola - Palma, Eduardo C (Cirugía del Uruguay, 1973)
Our case material for arterial occlusions comprises 211 patients and from it we gather that most frequent causes are thrombosis and embolisms. Treatment for the latter is surgical; in aorto-iliac embolisms, approach should be extraperitoneal. Forgarty's probe is not considered essential. In acute thrombosis initial medical treatment should be followed at an early stage by surgery and tactics should vary according to location of occlusion.